Neurons and Glia Cells: Some Mention of their General Interrelationships - Roberto Dotti (National Dong Hwa University, 2025)
In the present work we outline a hypothesis on what the role of glia cells could be in several operations processed by our brain. Going beyond the classical concept that attributes an almost ancillary function to glia at the service of neurons, and on the basis of what emerges from a lot of more or less recent studies about the possible glia-neuron collaboration in supporting many and diversified organic events, we intend to show how this functional synergy could be reasonably imagined as fundament of specific organic and mental processes both in the ordinary activity perspective and in the horizon of psycho-physical performances of higher level, where the exact meaning of psycho-physical performances of higher level will become later. In the frame of an evolutionary view of the human organism–considered in its wholeness–and of an evolution characterized by an increasing structural complexity, our aim is to present the idea (having to be carefully tested and developed in other contexts) according to which each organism is intimately driven to liberate itself from the contingency of the events occurring in the environment within which it is immersed. All this, in compliance with a general principle that seems to condition the living matter in its complex, that is, the principle of pursuing coenaesthesia, here generically conceived as the internal well-being which every organism wants to safeguard. The underlying persuasion is that evolution in complexity, tendency to a certain environmental emancipation and need for coenaesthesia, which the nature of living beings all together contains, can be better identified if we just begin to treat neurons and glia as a morphologic-functional unit that organically and systematically represents them.